Patients Experience and Perception in Preventing Tuberculosis Transmission in Rural Areas: A Qualitative Research - R Endro Sulistyono; Tantut Susanto; Rr Dian Tristiana (Faculty of Nursing Universitas Padjadjaran, 2020)
Tuberculosis (TB) transmission awareness is crucial for TB prevention in the community. However, efforts to prevent TB transmission from TB patients’ perspectives, especially in the rural area, are not well documented. This study aimed to explore the efforts made by TB patients in preventing transmission to the community. This research was qualitative research with a phenomenological approach. Participants in this study were 12 people selected by purposive sampling. Data collection was done by in-depth interviews and recorded. Data analysis was carried out by thematic analysis. This study produced seven themes: perception of TB disease, performing alternative treatments, using personal protective equipment, environmental modification, adhering to treatment, limiting interactions with others, and increasing food intake. Knowledge and awareness of TB patients are still an issue in preventing the transmission of TB in the community. Immediate intervention needs to be made regarding increasing knowledge and awareness of TB patients and the supervision of health workers regularly in handling TB disease in the community.